ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK, HARGA DAN DIFERENSIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PIZZA HUT DI JAKARTA BARAT - Nur Annisa Putri Sabrina; Elpawati E; Achmad Tjachja Nugraha (AGRIBUSINESS JOURNAL, 2018)
The development of science and technology causing the rapid economic sectors and culture also affected. The development in culture sectors also can’t be avoided, one example of the development in this sectors is a lot of fast food are sold in Indonesia. According to the new survey of Master Card (titled Consumer Purchasing Priorities) contained in Suara Pembaharuan 2016, 805 Indonesian’s people prefer to eat on the fast food outlet, in the second rank are food court with 615, and in the third rank are middle class restaurant or cafe with 225. Meanwhile, there is 1% Indonesian’s people who choose to come to restaurant for fine dining. Pizza Hut is the first fast food in Indonesia which serve pizza as a main dish. Consumer’s behaviour is the most to be considered remember all of that company did constituted by the market demands. Purpose of this research are to (1) know the characteristic of Pizza Hut consumer in West Jakarta; (2) know the influence of brand image to decision purchase of Pizza Hut in West Jakarta; (3) know the influence of product quality to decision purchase of Pizza Hut in West Jakarta; (4) know the influence of prices to decision purchase of Pizza Hut in West Jakarta; and (5) know the influence of product diferentiation to purhase decision of Pizza Hut in West Jakarta. Based on result in this research, characteristic of Pizza Hut consumer are consumer with the age range of the 20-30 years, women, with employment status is student or college student, know about pizza hut product from banner or commercial advertisement and buy pizza hut just one time in a month. Result of regression multiple linear analysis are brand image, product quality and product diferentiation are not significant influence to purhase decision of pizza hut in trust rate of 95%. Although of that, prices is significant influence to purchase decision of Pizza Hut product in West Jakarta.